2012
DOI: 10.1002/cctc.201200388
|View full text |Cite
|
Sign up to set email alerts
|

A Palladium Bipyridyl Complex Grafted onto Nanosized MCM‐41 as a Heterogeneous Catalyst for Negishi Coupling

Abstract: The Negishi coupling of aryl bromides or acyl chlorides with organozinc chlorides catalyzed by a palladium bipyridyl complex anchored on nanosized mobile crystalline material 41 (MCM‐41) were investigated. The reactions proceeded smoothly with a very low catalyst loading in THF at 70 °C for electron‐deficient aryl bromides, which gave good to high yields of the Negishi coupling products. However, reactions in toluene at 110 °C were required if electron‐rich aryl bromides were employed. For acyl chlorides, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…al. report the synthesis of anthracene derivatives using Negishi coupling of aryl halides with organozinc chlorides catalyzed by a palladium bipyridyl complex . Herein, we report an efficient one pot synthesis of 9‐arylmethylanthracene from vinylarenes, aryl iodides and arylzinc reagents.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…al. report the synthesis of anthracene derivatives using Negishi coupling of aryl halides with organozinc chlorides catalyzed by a palladium bipyridyl complex . Herein, we report an efficient one pot synthesis of 9‐arylmethylanthracene from vinylarenes, aryl iodides and arylzinc reagents.…”
Section: Figurementioning
confidence: 99%
“…report the synthesis of anthracene derivatives using Negishi coupling of aryl halides with organozinc chlorides catalyzed by a palladium bipyridyl complex. [10] Herein, we report an efficient one pot synthesis of 9-arylmethylanthracene from vinylarenes, aryl iodides and arylzinc reagents. In this process, we utilize a Ni-catalyzed alkene dicarbofunctionalization reaction [11] in tandem with an acid-promoted cyclizationaromatization process to construct the 9-arylmethylanthracene scaffold.…”
mentioning
confidence: 99%
“…3(a). All the samples exhibit Langmuir type IV isotherms [23,24] which are characteristic feature of mesoporous materials. The isotherms of all Au/MCM-41 catalysts are identical to the isotherm of mesoporous MCM-41 ( Fig.…”
Section: Bet Surface Area and Pore Size Distribution Measurementsmentioning
confidence: 99%
“…3(a)). The nitrogen adsorption isotherms of mesoporous MCM-41 and Au/MCM-41 catalysts exhibit H4-type hysteresis loop corresponding to pores with narrow necks and wider bodies [25] and features a sharp step in the P/P 0 range of 0.6-0.9, the sharpness of this step is indicative of the uniformity of the pore-size [24], However, the hysteresis loops of all Au/MCM-41 catalysts become smaller, and position of the step shifts towards lower relative pressure in the range of 0.45-0.89 (as observed from the Fig. 3(a)), indicating that a smaller pore-size is formed.…”
Section: Bet Surface Area and Pore Size Distribution Measurementsmentioning
confidence: 99%
“…For example, in 2013, Wu et al [181] reported on the Negishi coupling of aryl bromides or acyl chlorides with organozinc chlorides catalyzed by a palladium bipyridyl complex anchored on nanosized mobile crystalline material 41 (MCM-41). For example, in 2013, Wu et al [181] reported on the Negishi coupling of aryl bromides or acyl chlorides with organozinc chlorides catalyzed by a palladium bipyridyl complex anchored on nanosized mobile crystalline material 41 (MCM-41).…”
Section: Recent New Developments 83mentioning
confidence: 99%